URGENSI “MODERASI BERAGAMA” UNTUK MENCEGAH RADIKALISME DI INDONESIA - Samho, Bartolomeus (Sapientia Humana: Jurnal Sosial Humaniora, 2022)
This paper aims to describe the reasons behind the importance of “religious moderation” to prevent radicalism in Indonesia. The method used in this paper is literature study (books, journals, encyclopedias, and dictionaries). The results of this study indicate that "religious moderation" has the opportunity to maintain the nobility of religion so that it remains relevant and significant for all ages. In conclusion, a significant and relevant religious vision and mission to bring beauty, peace, a sense of kinship and unity in social diversity becomes manifest in "religious moderation". Therefore, the call for "religious moderation" is imperative, namely: religion must be lived and practiced for the liberation of humans from extreme attitudes and actions that risk dehumanizing. In that perspective, religion should not be used as an instrument to justify destructive actions. Instead, make religion a source of creative inspiration to continuously improve the quality of human life everywhere.